Development of Kalibataku Fraction Board Media to Improve Student Learning Results and Interest in Fraction Material - Puspitasari, Putri; Murtono, Murtono; Mulyani, Mulyani (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2023)
Mathematics learning in basic education institutions is minimal in the use of learning media, and student's interest in mathematics is very low. The learning process using media is very influential in supporting students' interests and learning outcomes. This research aims to develop a Kalibataku fraction board media to increase interest and learning outcomes in mathematics learning about fractions. This research was carried out using the method of Research and Development (R&D) and using the ADDIE model. The research subjects involved were grade V students, totaling 7 students 2 experts, and 1 class teacher. The research instrument for collecting data uses questionnaires and tests. Data analysis uses ADDIE steps: analysis, design, development, implementation, and evaluation. The research results show that the media developed is suitable for use based on expert validation results. There is an increase in student interest and learning outcomes after using the developed Kalibataku fraction board media. Also received a positive response from educators who categorized the media as suitable for application in learning.